Multiphoton Path Entanglement by Nonlocal Bunching - Eisenberg, H. S.; Hodelin, J. F.; Khoury, G.; Bouwmeester, D. (Phys. Rev. Lett., 2005)
Multiphoton path entanglement is created without applying postselection, by manipulating the state of stimulated parametric down-conversion. A specific measurement on one of the two output spatial modes leads to the nonlocal bunching of the photons of the other mode, forming the desired multiphoton path entangled state. We present experimental results for the case of a heralded two-photon path entangled state and show how to extend this scheme to higher photon numbers.
Publisher: American Physical Society